A Note on Heat Type Polynomials Suggested by Jacobi Polynomials: Mumtaz Ahmad Khan, Abdul Hakim Khan, Manoj Singh - Team, Support (Thai Journal of Mathematics, 2012)
In the present paper an attempt has been made to investigate a new class of heat type polynomials suggested by Jacobi polynomials. Results analogous to Jacobi polynomials obtained by Srivastava [H.M. Srivastava, Note on certain generating functions for Jacobi and Laguerre polynomials, Publ. Inst. Math. (Beograd) (N.S.) 17 (31) (1974) 149–154] and Varma [V.K. Varma, Appell’s double hypergeometric function as a generating function of the Jacobi polynomials, Riv. Mat. Univ. Parma 8 (1967) 305–308] have also been obtained for this new class of heat type polynomials.